2012
DOI: 10.1136/ejhpharm-2012-000074.291
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of antibiotic use in a tertiary hospital in Nigeria

Abstract: Background Antibiotics are among the most commonly prescribed drugs in paediatrics. Due to an overall rise in healthcare costs, lack of uniformity in drug prescribing despite standard treatment guidelines and the emergence of antibiotic resistance, monitoring and control of antibiotic use is of growing concern and strict antibiotic policies are warranted. Purpose To access the prescribing pattern of antibiotic use in the treatment of prevalent paediatric diseases at Federal Medical Centre Owerri, to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…[ 27 ] Although the WHO standard value was obtained largely from adult outpatient settings across developing countries (with fewer pediatric prescriptions),[ 27 ] they remain the only valid reference standards available for such comparison. Compared to what was reported in similar studies in Ethiopia, Sierra Leone, Nigeria, and India,[ 5 6 17 18 19 30 31 32 ] the average of 2.1 drugs per encounter in this study is the lowest even though just slightly above the WHO standard. The difference between the finding in this study and these cited reports could, however, be attributed to differences in study methodology.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…[ 27 ] Although the WHO standard value was obtained largely from adult outpatient settings across developing countries (with fewer pediatric prescriptions),[ 27 ] they remain the only valid reference standards available for such comparison. Compared to what was reported in similar studies in Ethiopia, Sierra Leone, Nigeria, and India,[ 5 6 17 18 19 30 31 32 ] the average of 2.1 drugs per encounter in this study is the lowest even though just slightly above the WHO standard. The difference between the finding in this study and these cited reports could, however, be attributed to differences in study methodology.…”
Section: Discussioncontrasting
confidence: 86%
“…[ 17 ] Cole et al ., in Sierra Leone, reported 82.99% of prescriptions containing antibiotics, being also the second most commonly prescribed medicines. [ 18 ] In Nigeria, Anyanwu and Arigbe-Osula[ 19 ] found between 63.3% and 86.6% of prescriptions containing antibiotics, whereas the rate of antibiotic prescribing was higher for children aged 1–5 years compared to other groups combined. They also found that 80%–86% of antibiotics were parenteral and 80%–85.5% were prescribed from the hospital formulary with the most common being cephalosporins, penicillin, and aminoglycosides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic prescription practices vary widely between countries and healthcare facilities; factors which have been reported to influence antibiotic use includes infectious disease burden, prescription habit of clinicians, microbial resistance pattern, regulatory control, standard treatment guidelines, availability and economic factors [23][24][25][26][27][28][29][30][31]. In resource scarce setting where routine empirical antibiotic use is widespread, prescription pattern also vary widely [22].…”
Section: Introductionmentioning
confidence: 99%
“…In many healthcare facilities where laboratory services are available, antibiotic prescriptions are not routinely based on microbial sensitivity results a common cause of irrational use [26,41,44]. Many antibiotic prescription studies have reported both high levels of irrational use and an increasing level of resistance to commonly used antibiotics [23,45].…”
Section: Introductionmentioning
confidence: 99%